Locally Adapted Microstructures in an Additively Manufactured Titanium Aluminide Alloy Through Process Parameter Variation and Heat Treatment. Issue 2 (13th October 2022) - Moritz, Juliane; Teschke, Mirko; Marquardt, Axel; Stepien, Lukas; López, Elena; Brueckner, Frank; Walther, Frank; Leyens, Christoph
Abstract : Electron beam powder bed fusion (PBF‐EB/M) has been attracting great research interest as a promising technology for additive manufacturing of titanium aluminide alloys. However, challenges often arise from the process‐induced evaporation of aluminum, which is linked to the PBF‐EB/M process parameters. This study applies different volumetric energy densities during PBF‐EB/M processing to deliberately adjust the aluminum contents in additively manufactured Ti–43.5Al–4Nb–1Mo–0.1B (TNM‐B1) samples. The specimens are subsequently subjected to hot isostatic pressing (HIP) and a two‐step heat treatment. The influence of process parameter variation and heat treatments on microstructure and defect distribution are investigated using optical and scanning electron microscopy, as well as X‐ray computed tomography (CT). Depending on the aluminum content, shifts in the phase transition temperatures can be identified via differential scanning calorimetry (DSC). It is confirmed that the microstructure after heat treatment is strongly linked to the PBF‐EB/M parameters and the associated aluminum evaporation. The feasibility of producing locally adapted microstructures within one component through process parameter variation and subsequent heat treatment can be demonstrated. Thus, fully lamellar and nearly lamellar microstructures in two adjacent component areas can be adjusted, respectively. Abstract : By varying the applied parameters within one component during electron beam powder bed fusion of the titanium aluminide alloy TNM‐B1, spatial variations of aluminum content and microstructure are achieved. Through a two‐step heat treatment, fully lamellar and nearly lamellar microstructures and consequently different hardness values can be adjusted within the same part, thus proving the feasibility of local microstructural tailoring.